Significance of Bordetella bronchiseptica in Respiratory Tract Infections of Canines - Rose, Kh. Thanila; Rajesh, J. B.; Marwein, S. C.; Kar, P.; Behera, S. K.; Chethan, G. E.; Bayan, H.; Rao, J. M.; Sarma, K.; Prasad, H. (International Journal of Bio-resource and Stress Management, 2025)
Bordetella bronchiseptica is one of the major pathogens affecting canine respiratory tract. The agent is transmitted through aerosol mode, contact with contaminated faces or urine as well as through infected fomites. The agent affects all age groups and breeds of dogs. It is a contagious one that can transmit to other dogs easily and it’s having zoonotic potential. Because of all these reasons Bordetella bronchiseptica infection got attention of researchers. Bordetella bronchiseptica, a gram-negative cocci bacterium causes respiratory discomfort in dogs as well as other animals. The sequential synthesis of virulence factors decides the pathogenesis of B. bronchiseptica viz., adhesions, toxins, and other bacterial products that may alter host functions, facilitate immune evasion, or otherwise assist in transmission or survival BvgAS controls bacteria’s virulent components. B. bronchiseptica causes a variety of clinical signs which develop within 3 to 4 days of exposure and, may persist for up to 14 days. Signs are coughing, gagging or retching and mild serous oculo-nasal discharge. Affected dogs usually remain non–febrile, alert and active. B. bronchiseptica diagnosis depends on isolation, identification using biochemical, serological, and molecular techniques. Culture, isolation molecular diagnostics are required to fully understand the bacteria details. Precaution such as isolation before re-entering the population, routine monitoring for the emergence of clinical signs with the group, and quarantine protocols for dogs should be done. Additionally, obtaining vaccinations and taking precautionary measures can help in reducing the chances of getting the animal infected.